The Gordon Riots Revisited - Rogers, Nicholas (Historical Papers / Communications historiques)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1988)
AbstractThe 1780 protests against the Catholic Relief Act were the most violent andcontroversial disturbances of the eighteenth century and have predictably given rise toseveral historical interpretations. Early studies sought to emphasize the politicalimmaturity and deep sectarian prejudices of the common people and the anarchy anddegenerate character of the riots themselves. By contrast, George Rude, in his firstexploration of British crowds, insisted that the riots were more orderly and purposivethan historians had assumed. Set within the context of the emergent radical movement,the riots, according to Rude, drew their inspiration from radical elements in London'sProtestant Association and from antiauthoritarian notions of the “Englishman'sbirthright.” Directed initially against Catholic chapels and schools, the disturbancesdeveloped into a social protest against the rich and propertied.This essay adopts a different approach. Like Rude, it endorses the view that theriots seldom deviated from the cue of the Protestant Association. Despite thedrunkeness and almost festive air which accompanied the disturbances, the riotsconstituted a disciplined reprisal against the Catholic community and a Parliament thatrefused to bow before popular pressure. Indeed, the pattern of violence reveals thatrioters acted discriminately, directing their anger at Catholic chapels, houses, andschools and at the property of those sympathetic to Catholic relief. Only with the sackingof the gaols and distilleries did the disturbances deviate from their original objective and,even then, the degree of looting and lawlessness can be easily exaggerated.At the same time, the Gordon riots cannot be categorically viewed as a socialprotest against the rich. Although the targets of the crowd included a disproportionatenumber of prominent Catholics and parliamentary supporters of the Relief Act, theprime aim of the rioters was to immobilize the Catholic community and to intimidateParliament. To be sure, elements of social protest did accompany the disturbances. Inthe carnivalesque freedom of the occasion participants sometimes showed a sardonicdisrespect for rank. Moreover, the opening of the gaols, initially to rescue imprisonedrioters, denoted an almost Brechtian contempt for the prison system and the law ingeneral. In the final phases of the riot, however, the social hostilities of the crowd wereessentially local and concrete, directed against crimps, debtors' lockups, and toll bridges.That is, they addressed the customary oppressions of the poor, not a generalised form ofsocial levelling.Nor were the riots closely associated with radical politics. Although some Londonradicals sympathised with the protesters in the initial stages of the disturbances, others,influenced by Enlightenment ideas, clearly did not. In fact, many were deeply troubledby the riots, fearing their excesses would prejudice popular movements in general.Basically the protests against the Catholic Relief Bill cut across traditional politicalalignments. Ideologically the Protestant Association was remarkably protean, drawingsupport from proministerial, but evangelical, conservatives as well as from radicalstroubled by ministerial incursions upon liberty in Britain and America. Ultimately theanti-Catholic protests of 1780 pitted a cosmopolitan social elite against a moretraditional rank and file fuelled by an evangelical fear of an incipient Catholic revival. Insum, the Gordon riots drew upon populist, nationalist sentiments that did not squarewith conventional political alignments. It remained to be seen how these forces could beaccomodated in contemporary political discourse.